Prevalence of non-spinal pathology and red flag diagnoses associated with care seeking for low back pain in the Military Health System - Daniel I. Rhon; Nathan A. Parsons; Riley Boeth; Xiaoning Yuan (Scientific Reports, 2026)
Abstract To identify potential red flag diagnoses in a cohort of patients seeking care for LBP, compare prevalence rates based on the setting of initial diagnosis, and identify demographic risk factors. A longitudinal cohort study using US Military Health System Data Repository data, identifying all patients seeking care for LBP in military clinics between January 2015 and December 2019. LBP cases and red-flag conditions were identified using diagnostic codes in electronic medical records. The setting of initial LBP diagnosis was also identified (immediate care: emergency/urgent care clinics, versus all others). 1,214,604 individuals sought care for LBP and met study criteria (37.7% female, 55.3% active duty, mean age: 34.7 years), with 10.2% initially seen in immediate care settings. A total of 2.9% of patients received a red-flag diagnosis within 90 days of the index LBP visit, ranging from 0.02% for cauda equina syndrome, vertebral fracture, abdominal aortic aneurysm, and ankylosing spondylitis to 1.2% for infection. Immediate care as the setting of initial LBP diagnosis, female sex, non-active-duty, and increasing age increased the odds for most red flag diagnoses. In patients seeking care for LBP, serious pathology was uncommon; only 2.9% with red flag diagnoses (3.2% immediate care versus 2.2% other settings). The rate of red flag diagnoses was significantly higher among patients initially seen in immediate care, except for cancer, gynecological disorders, and ankylosing spondylitis. Active-duty service members had higher odds for vertebral fractures and cancer, while males had higher risk for abdominal aortic aneurysm.